Endoscopic Removal of Neonatal Acute Epidural Hematoma via Strip-Bending Osteoplastic Craniotomy. Technical Note - Nakatogawa, Hirokazu; Tanaka, Tokutaro; Inenaga, Chikanori; Fujimoto, Ayataka; Yamamoto, Takamichi (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2015)
We present a rare case of an acute epidural hematoma extending through a skull fracture into a cephalohematoma in a neonate. The epidural hematoma was caused by a fall after delivery. The neonate remained neurologically asymptomatic. A computed tomography scan 12 days after delivery showed the large-volume epidural hematoma with midline shift. We performed a strip-bending osteoplastic craniotomy and removed the epidural hematoma and external cephalohematoma under neuroendoscopic control. This is the first reported case of an acute epidural hematoma in a neonate treated successfully neuroendoscopically via a strip-bending craniotomy.
Keywords: acute epidural hematoma; neonate; neuroendoscope; delivery trauma; strip-bending osteoplastic craniotomy